THE ROLE OF INNOVATIVE INFORMATION TECHNOLOGIES IN ENSURING STATE BORDER SECURITY (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article analyzes the strategic importance and relevance of implementing modern information technologies within the state border protection system. It highlights the role of the “Smart Border” concept, artificial intelligence, unmanned aerial systems, geographic information systems, biometric identification, and big data analytics in enhancing border security frameworks.
Keywords: State border, national security, information technologies, digital transformation, artificial intelligence, Smart Border, biometric identification, GIS, Big Data, unmanned aerial systems.